ANALISIS SEKTOR UNGGULAN KABUPATEN PANGANDARAN - Arifin, Farid (Bina Ekonomi, 2025)
The Local Government needs to carry out economic development appropriately, to achieve this goal the local government needs to accelerate the process of improving the regional economy by considering the potential of the region. This research was conducted with the aim of identifying the economic sectors of new autonomous regions such as Pangandaran Regency. The research method used in this research is descriptive quantitative, using the Location Quotient typology class and Shift-share analysis. The results of the study found that the Location Quotient Typology Analysis shows that the leading and potential sectors in Pangandaran Regency are the wholesale and retail trade sector; the car and motorcycle repair sector, the transportation and warehousing sector, the accommodation sector and the provision of food and beverages, the real estate sector, the corporate services sector, the government administration sector, defence, and the mandatory social security and education services sector. Based on the results of the shift-share analysis, it is known that the water supply, waste management, waste and recycling sector, transport and warehousing sector, accommodation and food supply sector, real estate sector, corporate services sector, and other services sector, are sectors that are growing rapidly and have competitiveness in Pangandaran Regency.